'Emptying the cage, changing the birds': state rescaling, path-dependency and the politics of economic restructuring in post-crisis Guangdong. Issue 4 (3rd July 2016) - Lim, Kean Fan
ABSTRACT: This paper evaluates how economic restructuring in Guangdong is entwined with the politicisation of state rescaling during and after the global financial crisis of 2008. It shows how a key industrial policy known as 'double relocation' generated tensions between the Guangdong government, then led by Party Secretary Wang Yang, and the senior echelon of the Communist Party of China in Beijing. The contestations and negotiations that ensued illustrate the dynamic entwinement between state rescaling and institutional path-dependency: the Wang administration launched this industrial policy in spite of potentially destabilising effects on the prevailing national structure of capital accumulation. This foregrounds, in turn, the constitutive and constraining effects of established, national-level policies on local, territorially specific restructuring strategies.